Molecular imaging of glucose uptake in oral neoplasia following topical application of fluorescently labeled deoxy-glucose - Nitin, N. (2009)
The clinical value of assessing tumor glucose metabolism via F-18 Fluorodeoxyglucose (FDG) PET imaging in oncology is well established; however, the poor spatial resolution of PET is a significant limitation especially for early stage lesions. An alternative technology is optical molecular imaging, which allows for subcellular spatial resolution and can be effectively used with topical contrast agents for imaging epithelial derived cancers. The goal of this study was to evaluate the potential of optical molecular imaging of glucose metabolism to aid in early detection of oral neoplasia. Fluorescently labeled deoxyglucose (2-NBDG (2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-glucose)) was applied topically to tissue phantoms, fresh oral biopsies (n=32) and resected tumors specimens (n=2). High-resolution imaging results show that 2-NBDG can be rapidly delivered to oral epithelium using topical application. In normal epithelium, the uptake of 2-NBDG is limited to basal epithelial cells. In contrast high grade dysplasia and cancers show uptake of 2-NBDG in neoplastic cells throughout the lesion. Following 2-NBDG labeling, the mean fluorescence intensity of neoplastic tissue averages 3.7 times higher than that of matched non-neoplastic oral biopsies in samples from 20 patients. Widefield fluorescence images of 8-paired oral specimens were obtained pre- and post-labeling with 2-NBDG. Prior to labeling, neoplastic samples showed significantly lower autofluorescence than non-neoplastic samples. The fluorescence of neoplastic samples increased dramatically after labeling; the differential increase in fluorescence was on average 30 times higher in neoplastic samples than in normal samples. Topical application of 2-NBDG can therefore provide image contrast in both widefield and high-resolution fluorescence imaging modalities, highlighting its potential in early detection of oral neoplasia.